INTEGRATING INFORMATION AND COMMUNICATION TECHNOLOGY IN ELEMENTARY SCHOOLS: TEACHERS’ ATTITUDES AND BARRIERS - Suparjan Suparjan (Ta'dib, 2021)
Unquestionably, the rapid development of ICT has had a significant impact on various areas of human life including education in the past few decades. The use of Information and Communication Technology (ICT) to support educational activities in schools has increased significantly in several developing countries as in the case of Indonesia. The study aims to examine the attitudes of teachers of elementary schools located in all districts in West Kalimantan, one of the provinces on the Island of Kalimantan, Indonesia, towards ICT as a medium to support teaching and learning activities which includes the ease of use, effectiveness and satisfaction. This study investigates how elementary school teachers view ICT as a supporting tool for classroom learning activities and the barriers faced regarding the use of the technology in teaching and learning activities. A total of 102 elementary school teachers were involved in this investigation by acting in response to a questionnaire and 13 participants were selected voluntarily to take part in in-depth interviews about their attitudes on the use of ICT as a tool for educating activities and the barriers these teachers encountered. The findings indicate that elementary school teachers had a positive attitude towards the employment of ICT for instruction along with the various barriers they faced during teaching and learning activities.